Staying connected to your athletes during COVID-19 through virtual training - Corcoran, G.; Martin, R.; Sullivan, T. (International Universities Strength and Conditioning Association Journal, 2020)
Providing training options for teams and squads that train at the Bond University High Performance Training Centre during COVID-19 isolation and social distancing requirements, to ensure they remain physically active and in preparedness for return to weight room lifting.